mondo travelأثر تحليل صوت الزبون في تحسين الأداء التسويقي : دراسة العلامات التجارية في سوق الخدمات دراسة ميدانية بالوكالة السياحية - - مروى دراني; إيمان خثير (My University, 2021)
the ain of this study to identify the impact of customer voice on improving the marketing performance .we relied on customer marketing performance marketing performance indicators .and this study was conducted by the ……. Of souk ahras And we followed the appropriate sample method though the devlopement of questionnaire in the agency for a method and the number of sample was 30 individuals and we found a correlation relationship and significant impact to hear the voice of the customer on the improvement of marketing performance from the point of the view the sample of the institution. .................................................... ﺗﻬدف هذه الدراسة إلى التعرف على اثر سماع صوت الزبون في تحسين الأداء التسويقي للوكالات السياحية ،حيث اعتمدنا في دلك على مؤشرات الأداء التسويقي المتعلقة بالزبون وبالإسقاط على الوكالات السياحية ب ولاية سوق أهراس ،وقمنا بإتباع أسلوب العينة الملائمة من خلال قيامنا بوضع استمارة استبيان على مستوى الوكالة لمدة مل يقا رب الشهر وقد بلغ أفراد العينة 30 فردا وقد توصلنا إلى وجود علاقة ارتباط وتأثير ذات دلالة معنوية للالتزام بسماع صوت الزبون على تحسين الأداء التسويقي من وجهة نظر أفراد العينة للوكالة محل الدراسة. .................................................. le but de cette etude est didentifier limpact de la voix du client sur lamelioration de performance marketing de lagence touristique .nous sommes appuyes sur des indicateurs de performance maarketing client .et cette etude a été realisee par les agence touristique de souk ahras . Lagence pendant un mois .le nombre dechantillons appropriee en elaborant un questionnaire dans une relations de correlation et un impact significatif pour entendre la voix du clients sur lameloration des performance marketing .du point de vue lechantillion de linstitution .